El analfabetismo digital en Ecuador a nivel sociodemográfico: Un enfoque estadístico y econométrico, año 2023. - Armijos Rivas, Rodin Wilfrido (2025)
Access to the Internet and new technologies allows improving human capital, and therefore achieving a higher lifestyle, enjoying better jobs, higher quality education and productivity as soon as digital inclusion can be granted, as opposed to vulnerable sectors and those with economic limitations (UNESCO, 2016). In the case of Ecuador, in July 2022, only 6 out of 10 Ecuadorian households had internet access (INEC, 2022). Therefore, this research aims to assess whether the sociodemographic level affects Digital Illiteracy in Ecuador, year 2023. For the present study, information was processed from 21 provinces of Ecuador, from the National Survey of Employment, Underemployment and Unemployment (ENEMDU, 2023) and the Technological Survey (TIC, 2023) published by INEC (2023). Econometric techniques of multiple regression, probabilistic model (Probit) and marginal effects were used. The main results indicate a positive relationship between socio-demographic level and digital illiteracy (having access to the Internet), whose relationship improves if people have a higher level of schooling, are older, are mestizo and live in urban areas. It is important to mention that the gender variable showed a negative marginal effect of -0.0901, that is, being a woman reduces her probability of accessing the Internet by - 9.01% with respect to men. This reinforces the idea that policies are necessary to reduce the digital divide, not only by strengthening digital infrastructure, but also through initiatives that promote digital education. Therefore, it is essential to consolidate a technological innovation model that includes public-private partnerships and civil society.